Hope as a Mediator in the Relationship between Gratitude and Life Satisfaction among Science Students - Neni Trinovita; Kartika Nur Fathiyah; Halima Halima; Hadi Alhail (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to examine the effect of gratitude on life satisfaction among students and to investigate whether hope mediates this relationship. The study also sought to clarify the psychological mechanism through which gratitude contributes to life satisfaction. Methodology: This quantitative survey involved 475 science students selected using an accidental sampling technique. Data were collected using the Gratitude Questionnaire-6 (GQ-6), Snyder's Hope Scale (SHS), and the Satisfaction with Life Scale (SWLS). Mediation analysis with 5,000 bootstrap resamples was performed using Jamovi version 2.6. Main Findings: These findings suggest that efforts to improve adolescent life satisfaction need to consider developing hope in addition to gratitude. The findings showed that hope significantly mediated the relationship between gratitude and life satisfaction. The indirect effect of gratitude on life satisfaction through hope was significant (β = 0.28379, p < 0.001), whereas the direct effect became non-significant after hope was included in the model (β = −0.00332, p = 0.955), indicating full mediation. These findings suggest that gratitude contributes to students' life satisfaction primarily by strengthening hope. Novelty/Originality of this study: This study provides empirical evidence that hope functions as a full mediator in the relationship between gratitude and life satisfaction among students. The findings extend the application of Hope Theory by clarifying the psychological mechanism through which gratitude enhances life satisfaction and provide practical implications for developing interventions that integrate gratitude and hope to promote students' psychological well-being.